2002
DOI: 10.1007/s00210-002-0537-y
|View full text |Cite
|
Sign up to set email alerts
|

Delayed cardioprotection induced by nitroglycerin is mediated by alpha-calcitonin gene-related peptide

Abstract: Previous investigations have demonstrated that early preconditioning induced by nitroglycerin is mediated by calcitonin gene-related peptide (CGRP). In the present study, we addressed the question of whether delayed preconditioning induced by nitroglycerin in the rat is related to stimulation of the release and synthesis of CGRP. Sprague-Dawley rats were pretreated with nitroglycerin 24 h before the experiment. The left main coronary artery was occluded for 60 min, followed by 3 h reperfusion. Infarct size, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Using capsaicin to deplete sensory nerves from CGRP, we showed that the induction of late anti-infarct and anti-arrhythmic effects of NTG is CGRP dependent. Zhou et al also observed a similar anti-infarct effect in the same animal model [17]. CGRP could lead to PKC translocation [15,26] so we hypothesized that NTG may trigger the late phase through PKC activation and the late phase will be abolished using PKC inhibiter, CHE.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Using capsaicin to deplete sensory nerves from CGRP, we showed that the induction of late anti-infarct and anti-arrhythmic effects of NTG is CGRP dependent. Zhou et al also observed a similar anti-infarct effect in the same animal model [17]. CGRP could lead to PKC translocation [15,26] so we hypothesized that NTG may trigger the late phase through PKC activation and the late phase will be abolished using PKC inhibiter, CHE.…”
Section: Discussionmentioning
confidence: 74%
“…Group 2 (NTG, n = 11), rats received only NTG [120 μg kg − 1 , iv (2 μg kg − 1 min − 1 iv over 1 h)] [13,17]. Group 3 (CHE + NTG, n = 11), rats received CHE (5 mg kg − 1 , iv), 10 min before NTG infusion.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Previous reports had shown that NO participated in delayed cardioprotection via a cGMP-dependent mechanism. 35,36 In the present experiment, MB, an inhibitor of guanylate cyclase, was used to investigate the role of NO-dependent activation of guanylate cyclase in the delayed preconditioning induced by NTG in rat small intestine. The results revealed that in vivo pretreatment with NTG caused not only an increase in blood concentrations of both CGRP and NO but also the CGRP mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were allocated into 4 groups: a-Control group, non-treated , b-GTN-treated group, rats received GTN intraperitoneal 25 minutes before sacrifice, in a dose of 120 μg/kg bw (Zhou et al, 2002) ,cVit E-treated group, rat received vitamin E by oral tubal feeding 16-20 hours before sacrifice, in a dose of 250mg/rat d-Vit E and GTN-treated group, rats received vitamin E and GTN as in both GTN-treated group and vit E -treated group.…”
Section: Methodsmentioning
confidence: 99%